Managerial communication - Bell, Reginald L. (2014 digital library., 2014)
Explores what the communication managers actually do in business across the planning, organizing, leading, and controlling functions. The top, middle, and frontline communications in which managers engage is also discussed. All of the levels of communication (intrapersonal, interpersonal, group, organizational, and intercultural) play a role in managerial communication; therefore, these levels are explained thoroughly in Chapter 2, but are relevant in all chapters. As we expound, for example, on theories of communication we relate them to the theories of management such as crisis management, impression management, equity theory, and effective presentation skills. These are the skills that are invaluable to management; you will begin to appreciate the depth and breadth of the painstaking effort we took to explicate these important topics. Our book, therefore, brings communication to the forefront of management theory because it is our belief that management cannot function without the particular techniques of communication covered in Managerial Communication.